Detection of circulating IgG aggregates and immune complexes using 125I protein A from Staphylococcus aureus. Issue 4 (August 1976) - Hällgren, R; Wide, L
Abstract : A method for detection of circulating immune complexes by the use of 125I labelled staphylococcal protein A is described. In a polyethylene glycol solution as little as 1-2 mg/l of soluble heat aggregated human IgG could be quantitated. Variables which might influence the assay were examined. Separation of immune complexes in serum from monomeric IgG was essential and achieved by gel chromatography on Sephadex G200. This assay may be suitable for clinical routine for detection and quantitation of immune complexes. A preliminary study on the clinical application of the method is presented. 58% of patients with systemic lupus erythematosus and 42% of patients with rheumatoid arthritis had increased levels of immune aggregates in serum compared to a group of healthy individuals.